NAMPT expression in osteoblasts controls osteoclast recruitment in alveolar bone remodeling. Issue 9 (16th April 2018) - Hassan, Bassam; Baroukh, Brigitte; Llorens, Annie; Lesieur, Julie; Ribbes, Sandy; Chaussain, Catherine; Saffar, Jean‐Louis; Gosset, Marjolaine
Abstract : In bone remodeling, osteoclasts are recruited via increased production of RANKL (receptor activator of nuclear factor‐κB ligand) and migrate to the bone surface, aided by matrix metalloproteinases (MMPs). NAMPT (nicotinamide phosphoribosyl transferase), which catalyzes the rate‐limiting step in the NAD + salvage pathway, increases during in vitro osteogenic differentiation and inhibits RANKL‐induced osteoclast differentiation. Alveolar bone loss, due to disturbance of the remodeling process, is a major feature of periodontitis. Thus, we investigated the role of NAMPT in a synchronized alveolar bone remodeling rat model. NAMPT expression increased in osteogenic cells during the remodeling activation phase, in parallel with RANKL and MMP‐2 expression. Inhibition of NAMPT activity, by systemic delivery of its selective inhibitor FK866, decreased the recruitment of osteoclasts, but not their activity. In vitro, NAMPT mRNA, and protein expression also increased during osteoblast differentiation in primary calvarial osteoblast cultures. Recombinant NAMPT and NMN, its direct metabolite, dose‐dependently increased bone marker expression, including that of sialoprotein (BSP) and osteocalcin (OC), whereas their expression was inhibited by FK866 treatment. Recombinant NAMPT did not regulate MMP‐2, −9, MMP‐13, or RANKL/OPG mRNA expression in osteoblasts. Our data suggest that de novo NAMPT synthesis in osteoblasts controls cell differentiation through osteoclast recruitment during the activation of bone remodeling. Abstract : Inhibition of NAMPT enzymatic activity using systemic FK866 delivery decreases osteoclast recruitment in the rat alveolar bone remodeling model.